2021
DOI: 10.3390/plants10112284
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the Homeobox Gene Family and Identification of Drought-Responsive Members in Populus trichocarpa

Abstract: Homeobox (HB) genes play critical roles in the regulation of plant morphogenesis, growth and development. Here, we identified a total of 156 PtrHB genes from the Populus trichocarpa genome. According to the topologies and taxonomy of the phylogenetic tree constructed by Arabidopsis thaliana HB members, all PtrHB proteins were divided into six subgroups, namely HD-ZIP, ZF-HD, HB-PHD, TALE, WOX and HB-OTHERS. Multiple alignments of conserved homeodomains (HDs) revealed the conserved loci of each subgroup, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Relevant studies of all transcription factors except HB-other have shown that they are associated with plant responses to abiotic stress [17,28,39]. While less research has been conducted on HB-other transcription factors in response to abiotic stress, studies in Populus and ground tipped melon have shown that HB-other transcription factors are associated with drought tolerance regulation in plants [40,41]. Therefore, regulation of the transcription factor HB-other may be important for CB9 to resist osmotic stress caused by saline-sodic stress and to maintain the growth metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies of all transcription factors except HB-other have shown that they are associated with plant responses to abiotic stress [17,28,39]. While less research has been conducted on HB-other transcription factors in response to abiotic stress, studies in Populus and ground tipped melon have shown that HB-other transcription factors are associated with drought tolerance regulation in plants [40,41]. Therefore, regulation of the transcription factor HB-other may be important for CB9 to resist osmotic stress caused by saline-sodic stress and to maintain the growth metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A Hidden Markov Model (HMM) was used to identify HD zip candidates in radish, and the HMM profiles of HD domain (PF00046) and LZ domain (PF02183) were downloaded from the Pfam protein database (http://pfam.xfam.org/) (Guo et al, 2021). The putative HD‐Zip proteins identified by HMMER v3 software (Hou et al, 2021) were submitted to the CDD database (https://www.ncbi http://nlm.nih.gov/cddhttps://blast.ncbi.nlm.nih.gov/Blast.cgi) to check for complete HD and LZ domain (Zhang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%